Spanish Women''s Writing 1849-1996. - Davies, Catherine (Women in Context: Women''s Writing., 2000)
Traces the tradition of Spanish women''s writing from the end of the Romantic period until the present day. Professor Davies places the major authors within the changing political, cultural and economic context of women''s lives over the past century-and-a-half -- with particular attention to women''s accounts of female subjectivity in relation to the Spanish nation-state, government politics, and the women''s liberation movement.